"Burned into my Brain:" Trauma Anniversary Reactions Examined from a Qualitative Perspective. Issue 8 (17th September 2022) - Bruce, Madeline J.; Matsuo, Hisako
Abstract: Given the clinical significance of trauma anniversary reactions (ARs) but a dearth of empirical research on them, we conducted a qualitative study to identify major concepts deriving from interviews with those who endure ARs. Snowball sampling serendipitously recruited primarily women ( N  = 13) who endorsed ARs caused by interpersonal violence and related traumas. The resulting model detailed phases of experiences of ARs from the interviews conducted. Specifically, participants reported a waxing and waning of PTSD symptoms, and their experiences reflected major concepts of self-reflection, social connection, and making meaning of the trauma. We discuss ways results of this study could motivate future study, such as conceptualizing ARs from existential and logo-therapeutic traditions.